Pengaruh Penambahan Serat Bambu terhadap Kuat Tekan Beton - Valentinus Wenang Trisno Jati; Destiana Safitri; Fajar Dewantoro (Jurnal Konstruksi, 2025)
Fiber concrete is an innovation in concrete technology that utilizes additional materials in the form of natural or synthetic fibers to improve its mechanical characteristics, such as tensile strength, crack resistance, and ductility. In this study, K150 grade concrete was used with four variations of bamboo fiber addition: 0% (as a control), 0.5%, 1%, 1.5%, and 2% by weight of cement. Compressive strength tests were conducted at 14 and 28 days. The results showed that the addition of bamboo fibers consistently increased the compressive strength of the concrete. This increase was associated with better bonding between the aggregate and cement paste, which increased the density and strength of the material. At 14 days, concrete without fiber achieved a compressive strength of 10.57 N/mm², while concrete with 2% bamboo fiber achieved 15.94 N/mm². At 28 days, the respective values were 12.91 N/mm² and 17.85 N/mm². The average increase was 26.15% compared to the control concrete. Further research is recommended to explore higher fiber content and the use of various types of bamboo to evaluate the comparison of compressive strength performance. This study contributes to the development of environmentally friendly concrete by utilizing sustainable local materials.